Migrants' Rights, Populism and Legal Resilience in Europe - Stoyanova, Vladislava; Smet, Stijn (Social Sciences, 2022)
Analysing the problematic interplay between the rise of populism, restrictions of migrants' rights and democratic decay in Europe, this book goes beyond diagnosis by examining the potential for legal resilience. Bringing together scholars from migration and constitutional law, it provides a nuanced account for scholars and advanced students.